New oxindole alkaloids from Gelsemium elegans. Issue 45 (4th November 2015) - Sun, Ming-Xue; Gao, Huan-Huan; Zhao, Jie; Zhang, Lei; Xiao, Kai
Graphical abstract: Abstract: A group of indole alkaloids, gelsepyrrodines A–C (1 –3 ), with a new gelsedine skeleton incorporated with a pyrrole ring, were isolated from the roots of Gelsemium elegans Benth. Their structures were elucidated by spectroscopic analysis and single-crystal X-ray diffraction. Biological activity experiment showed that gelsepyrrodine B (2 ) could significantly decrease the chloride ion current evoked by GABA in rat neurons. This study provided direct evidence that the Gelsemium alkaloids could exert their activity through GABAergic system and therefore, shed some light on the toxicological mechanisms of the Gelsemium alkaloids.